Evaluation of Remaining Gas Reserves Using the Material Balance Method for Planning Gas Field Development - Dyah Rini Ratnaningsih; Ahmad Muraji Suranto; Cahyadi Julianto (Universitas Islam Riau (UIR) Press, 2022)
The demand of energy in the world will increase due to the increasing population and industrial activity. Currently, the fossil energy is relatively cheaper compared to other energy sources, especially natural gas. The “CJ” field is a gas field located in the South Sumatra Basin, Indonesia with a reservoir located in the Basalt Telisa Limestone (BTL) formation. This gas field consists of 3 wells namely Well GTA-1, GTA-2, and GTA-3 which produced from 1951 to 1991. In 1991 the three wells were suspended and will be reopened in 2021 due to request from buyers for 10 years. The research method is collecting and consisting of data on reservoir, production, and physical properties of the gas. The next step is to calculate the value of the gas formation volume factor and Z-factor (gas compressibility factor/gas deviation factor) with various pressures. After it, determine the type of drive mechanism using the Cole Plot method. After knowing the type of drive mechanism, determine the current OGIP value using the material balance method. If the OGIP value is known, the next calculation is the Recovery Factor (percentage of the amount of gas that can be produced to the surface), Ultimate Recovery (UR) and finally the value of Remaining Reserve (RR). Based on the calculation, the OGIP value obtained by the material balance method with P/Z vs GP plots is 83.46 BSCF, Recovery Factor of 80.22%, Ultimate Recovery of 66.96 BSCF, and remaining gas reserve 15.45 BSCF. The maximum flow rate could be obtained by remaining reserve divided contract period. From these results, the maximum reserve value that can be produced to the surface for 10 years is 4.23 MMSCFD. Therefore “CJ